A BCR/ABL-hIL-2 DNA Vaccine Enhances the Immune Responses in BALB/c Mice. (6th June 2013) - Qin, Yanan; Tian, Hongxia; Wang, Guanming; Lin, Chen; Li, Yangqiu
Abstract : The use of a DNA vaccine encoding the BCR/ABL fusion gene is thought to be a promising approach for patients with chronic myeloid leukemia (CML) to eradicate minimal residual disease after treatment with chemotherapy or targeted therapy. In this study, our strategy employs genetic technology to create a DNA vaccine encoding the BCR/ABL fusion and human interleukin-2 (hIL-2) genes. The successfully constructed plasmids BCR/ABL-pIRES-hIL-2, BCR/ABL-pIRES, and pIRES-hIL-2 were delivered intramuscularly to BALB/c mice at 14-day intervals for three cycles. The transcription and expression of the BCR/ABL and hIL-2 genes were found in the injected muscle tissues. The interferon- γ (IFN- γ ) serum levels were increased, and the splenic CD4 + /CD8 + T cell ratio was significantly decreased in the BCR/ABL-pIRES-hIL-2-injected mice. Furthermore, specific antibodies against K562 cells could be detected by indirect immunofluorescence. These results indicate that a DNA vaccine containing BCR/ABL and hIL-2 together may elicit increased in vivo humoral and cellular immune responses in BALB/c mice.